Buttressing Salicylaldehydes: A Multipurpose Directing Group for C(sp3)−H Bond Activation. Issue 4 (19th December 2016) - Yada, Akira; Liao, Wenqing; Sato, Yuta; Murakami, Masahiro
Abstract: A palladium‐catalyzed reaction of primary amines with iodoarenes produces γ‐arylated primary amines. A bulky salicylaldehyde, which is marked as easily available, installable, removable, and recoverable, plays a key role in directing palladium to site‐selectively activate the C−H bond located γ to the amino group. Abstract : Added bulk : A palladium‐catalyzed reaction of primary amines with iodoarenes produces γ‐arylated primary amines. A buttressing salicylaldehyde, which is easily available, installable, removable, and recoverable, plays a key role in directing palladium to site‐selectively activate the C−H bond located γ to the amino group.